PENGEMBANGAN MEDIA KOMIK MENYAJIKAN PERUBAHAN DIALOG MENJADI TEKS PROSEDUR DI KELAS IX MTS AL-‘IMAROH CIKARANG UTARA - Sultonah, Nur Sultonah; Lestari, Dinda Permata; Alfath, Khoirunnisa Syahadati; Rosalina, Sinta (STKIP PGRI SUMENEP, 2025)
This study aims to develop comic-based learning media for ninth-grade students at MTS Al-'Imaroh Cikarang Utara. The comic, adapted from the short story